(3QSGdI ajgG GdGSe GdCYXe hbUjOI GdEeGe Ydj dOaY GdWGYhf hGdOGFQI GdfGaYIs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3hHYO agPg ebOeJgG defXheI ef cdGe CejQ GdeDefjf hbkWH GdYGQajf Pj GdefGbH GdeTghQI CejQ GdeDefjf CHj GdMSfjf Ydj Hf CHj WGdH cQe Gddg hLgg s
(3BNQgG (B:s
(3hgPg GdOGFQI EP gj ef GdahGFO GdJj de jSeM GdReGf HeKdgG , hgPG eG GfJgi Edjg GdcdGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B821) s
Keywords: (3GdMQha h GdChaGbs